Preparation method of modified starch-based intumescent flame retardant taking itaconic acid as bridge

By using itaconic acid to chemically react with materials such as DOPO and starch, a modified starch-based one-component expansion flame retardant was prepared, which solved the problem of PLA flammable and the use of toxic solvents for existing flame retardants, and achieved high efficiency , environmentally friendly flame retardant effect.

CN119462973AActive Publication Date: 2025-02-18FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411678368.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Polylactic acid (PLA) materials are flammable and produce a large number of melt droplets during combustion, which limits its application range. The existing flame retardants use toxic solvents and are inefficient.

Method used

Itaconic acid is used as a bridge to add reaction with 9,10-dihydro-9-oxa-10-phosphazepamphene-10-oxide (DOPO) through its unsaturated double bond, and itaconic acid is used. The two carboxyl groups undergo esterification and amidation reaction with starch and melamine phosphate respectively to prepare a modified starch-based one-component expansion flame retardant.

Benefits of technology

After the flame retardant is added to PLA, it can effectively suppress smoke and prevent secondary combustion caused by melt droplets. It has high flame retardant efficiency, good compatibility and mechanical properties. The raw materials are renewable green resources and are cheap. No toxic solvents are required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462973A_ABST
    Figure CN119462973A_ABST
Patent Text Reader

Abstract

The invention discloses a modified starch-based single-component intumescent flame retardant taking itaconic acid as a bridge as well as a preparation method and application of the modified starch-based single-component intumescent flame retardant. Starch, itaconic acid, DOPO (9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), phosphoric acid and melamine are used as raw materials, and the'three-source-in-one 'modified starch-based single-component intumescent flame retardant is prepared by a one-pot method. The preparation process of the flame retardant is simple and safe, most of the raw materials are derived from low-cost, green and renewable biomass materials, the flame retardant is environment-friendly and high in compatibility with polymers, when the flame retardant is applied to PLA, the influence on the mechanical performance of the materials is small, the degradation performance of PLA can be improved, the flame retardant efficiency is high, and the flame retardant is suitable for industrial production. And melt droplet and dense smoke emission can be effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer flame retardancy, and specifically relates to the preparation and application of a modified starch-based single-component intumescent flame retardant using itaconic acid as a bridge. Background Art

[0002] Polylactic acid (PLA) is a synthetic polymer material with good biocompatibility and biodegradability. It is a biodegradable material made from crops as the initial raw material, which is decomposed into glucose under the action of enzymes, then fermented by lactic acid bacteria to obtain lactic acid, and finally polymerized. In addition to its significant degradability, PLA also has excellent mechanical properties, processing convenience, high transparency and good biocompatibility. These characteristics make polylactic acid widely used in many fields such as electronic product packaging, textiles, and medical treatment. However, the flammability of PLA and the large amount of droplets produced when it burns limit its application. Therefore, flame retardant modification of PLA becomes very important. Traditional PLA flame retardants mainly include halogen flame retardants, nitrogen flame retardants, phosphorus flame retardants, and intumescent flame retardants. In recent years, biomass-based intumescent flame retardants have gradually come into people's sight due to their good biocompatibility, green environmental protection, and better flame retardant effect with less addition.

[0003] Starch is one of the most abundant polysaccharides in nature. It is cheap, has abundant -OH groups, and can undergo a variety of chemical reactions. The combustion process of starch is similar to thermal degradation. It is easily catalyzed into carbon by acid sources, forming a dense carbon layer to protect the matrix, so it can be used as a stable carbon source. At the same time, starch combustion will decompose and release inert gases such as CO2, which inhibits thermal oxygen exchange. However, the phosphorylation reaction of starch itself requires the use of toxic solvents (DMF) for catalysis and is extremely inefficient.

[0004] Itaconic acid (IA) is the fifth largest organic acid in the world. Its molecular structure has two carboxyl groups and one unsaturated double bond, which makes it have very active chemical properties and can undergo addition reactions, esterification reactions and amidation reactions. At present, the production of itaconic acid is mainly based on fermentation. It is obtained by using agricultural and sideline products such as starch, sucrose, and sawdust as raw materials, adding nitrogen sources, inorganic salts, etc. for appropriate fermentation. Its annual output is about 100,000 tons. It is relatively cheap and belongs to renewable resources. Therefore, using itaconic acid as a bridge for the synthesis of modified starch-based single-component intumescent flame retardants can avoid the use of toxic reagents and improve the synthesis efficiency of flame retardants on the one hand, and on the other hand, it is of great significance to the commercialization of modified starch-based single-component intumescent flame retardants.

[0005] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) has abundant PH bonds and gas-phase flame retardant properties, and is often used in synergistic flame retardant polymer materials with other biomass materials. The flame retardancy of DOPO is mainly achieved through two pathways: gas-phase flame retardancy and solid-phase flame retardancy. In the chemical gas-phase flame retardant process, the combustion of polymers will produce a large number of free radicals, such as H· and ·OH. In the phosphorus-containing flame retardant system, the free radicals such as PO·, PO2 and HPO· produced by the thermal decomposition of DOPO can capture H· and ·OH and effectively extinguish the flame; at the same time, the formation of phosphorus oxygen free radicals in DOPO is easier than the formation of phosphate products, which means that more P elements in DOPO will be consumed in the gas phase. Physical gas-phase flame retardancy is that the pyrolysis of DOPO produces more non-flammable gases (H2O and CO2, etc.), which can dilute O2 and combustible gases. The condensed phase flame retardancy of DOPO is mainly achieved by protecting the polymer surface through phosphoric acid and polyphosphoric acid produced by the decomposition of some phosphorus-containing compounds, and preventing the molten adhesive layer from oxygen penetration. This process can significantly limit the molten dripping rate of the composite material under high heat conditions, thereby controlling the spread of flame and combustion.

[0006] The present invention utilizes the unsaturated double bond of itaconic acid to react with DOPO for addition reaction, and utilizes the two carboxyl groups of itaconic acid to react with starch and melamine phosphate for esterification and amidation reaction, respectively, to obtain a modified starch-based single-component intumescent flame retardant integrating acid source, carbon source and gas source. The novel flame retardant has appropriate C, N and P contents, high flame retardant efficiency, can effectively suppress smoke and prevent secondary combustion caused by molten droplets, its raw materials are renewable green resources, low cost and no toxic solvents are needed, it has high commercial value, and has broad application prospects and economic value. Summary of the invention

[0007] The purpose of the present invention is to provide a modified starch-based single-component intumescent flame retardant using itaconic acid as a bridge, and a preparation method and application thereof. The flame retardant prepared by the invention has the advantages of using renewable materials, good thermal stability, strong compatibility with PLA, high flame retardant efficiency, anti-melting dripping and anti-smoke, etc., and has broad application prospects and application value in PLA.

[0008] To achieve the above object, the present invention adopts the following technical solution: A modified starch-based single-component intumescent flame retardant with itaconic acid as a bridge is prepared by a one-pot method using starch, itaconic acid (IA), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), phosphoric acid and melamine as raw materials; the synthesis route is as follows: .

[0009] The preparation of the modified starch-based single-component intumescent flame retardant comprises the following steps: (1) Add starch to deionized water and stir magnetically at room temperature to obtain a starch suspension; (2) slowly adding itaconic acid and DOPO into anhydrous ethanol and stirring to react to obtain a DOPO-modified itaconic acid solution; (3) adding melamine to deionized water, stirring evenly to obtain a suspension, and then adding phosphoric acid to react to obtain a melamine phosphate solution; (4) adding the starch suspension obtained in step (1) dropwise into the DOPO-modified itaconic acid solution obtained in step (2), and obtaining a DOPO-modified starch suspension with itaconic acid as a bridge by stirring and reacting; (5) The melamine phosphate solution obtained in step (3) is added dropwise to the DOPO modified starch suspension obtained in step (4); after stirring for reaction and aging at room temperature, the mixture is vacuum filtered, washed, dried, and crushed to obtain a modified starch-based single-component intumescent flame retardant with itaconic acid as a bridge.

[0010] Furthermore, the starch in step (1) is one or more of soluble starch and water-soluble starch.

[0011] Furthermore, the molar ratio of itaconic acid to DOPO used in step (2) is 1:1.

[0012] Furthermore, the stirring reaction in step (2) is carried out at a temperature of 90° C. and for a time of 2 h.

[0013] Furthermore, the molar ratio of melamine to phosphoric acid used in step (3) is 1:(1-2).

[0014] Furthermore, the reaction temperature in step (3) is 70-100°C and the reaction time is 2 h.

[0015] Furthermore, the amount of the DOPO-modified itaconic acid solution used in step (4) is calculated based on the molar ratio of DOPO to starch being 1:(1-2).

[0016] Furthermore, the stirring reaction in step (4) is carried out at a temperature of 120° C. and for a time of 1.0-2.0 h.

[0017] Furthermore, the amount of the melamine phosphate solution used in step (5) is converted based on a molar ratio of melamine to DOPO of 1:1.

[0018] Furthermore, the stirring reaction in step (5) is carried out at a temperature of 70-100°C and for a time of 2 h.

[0019] Furthermore, the aging time in step (5) is 12-24 h.

[0020] Furthermore, the drying temperature in step (5) is 70-100°C and the drying time is 12-24 h.

[0021] Furthermore, the stirring rate in steps (1) to (5) is 200-500 rpm.

[0022] The modified starch-based single-component intumescent flame retardant can be applied to PLA, specifically by adding the modified starch-based single-component intumescent flame retardant to PLA, and the added amount is 5%-15% of the mass of PLA.

[0023] The significant advantages of the present invention are: (1) The modified starch-based single-component intumescent flame retardant with itaconic acid as a bridge of the present invention uses starch, one of the most abundant polysaccharides in nature, as a main raw material. The raw material source is wide and green and environmentally friendly. The synthesis of the flame retardant is completed in the water phase, the preparation process is simple, and it is easy to realize industrial production.

[0024] (2) The present invention uses itaconic acid as a bridge, utilizes its unsaturated double bond to undergo addition reaction with DOPO, and utilizes its two carboxyl groups to undergo esterification reaction and amidation reaction with starch and melamine phosphate, respectively, to obtain a modified starch-based single-component intumescent flame retardant that integrates an acid source, a carbon source, and a gas source. The flame retardant is pure white and has no effect on the appearance of the PLA composite material after processing.

[0025] (3) The modified starch-based single-component intumescent flame retardant of the present invention has appropriate C, N, and P contents and high flame retardant efficiency. When the amount thereof added to PLA is 10 wt%, the flame retardant grade can reach UL94 V-0, and it can effectively prevent molten dripping and thick smoke emission. In addition, it has strong compatibility with polymers and has little effect on the mechanical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 FT-IR images of the modified starch-based one-component intumescent flame retardant prepared in Examples 1 and 2, starch (SST), and melamine (MEL).

[0027] Figure 2 This is a SEM image of the char layer of the flame retardant sample prepared by adding the flame retardant obtained in Example 1 after combustion.

[0028] Figure 3 This is a SEM image of the carbon layer of the flame retardant sample prepared by adding the flame retardant obtained in Example 2 after combustion.

[0029] Figure 4 This is a SEM image of the carbon layer of the combustion specimen after combustion prepared by adding the flame retardant obtained in the comparative example and the starch mixture.

[0030] Figure 5This is the SEM image of the char layer after combustion of the combustion specimen prepared with only starch added.

[0031] Figure 6 This is the SEM image of the carbon layer of the pure PLA combustion specimen after combustion.

[0032] Figure 7 The 90-day degradation data change chart of the degradation specimen prepared by adding the flame retardant obtained in Example 1, starch and pure PLA. DETAILED DESCRIPTION

[0033] A modified starch-based single-component intumescent flame retardant using itaconic acid as a bridge, the preparation of which comprises the following steps: (1) Add starch to deionized water and stir magnetically at room temperature to obtain a starch suspension; (2) Slowly adding itaconic acid and DOPO in a molar ratio of 1:1 into anhydrous ethanol and stirring at 90 °C for 2 h to obtain a DOPO-modified itaconic acid solution (DOPOIA solution); (3) Add melamine to deionized water and stir to obtain a suspension, then add phosphoric acid at 70-100 °C and react for 2 h to obtain a melamine phosphate solution; (4) adding the starch suspension obtained in step (1) dropwise into the DOPO-modified itaconic acid solution obtained in step (2), and reacting the mixture at 120° C. with stirring for 1.0-2.0 h to obtain a DOPO-modified starch suspension with itaconic acid as a bridge; (5) adding the melamine phosphate solution obtained in step (3) to the DOPO modified starch suspension with itaconic acid as a bridge obtained in step (4), stirring and reacting at 70-100° C. for 2 h to obtain a DOPO / melamine / phosphate modified starch suspension; (6) The suspension obtained in step (5) is allowed to stand for 12-24 h, then filtered and washed three times, dried in a vacuum oven at 70-100 °C for 12-24 h, and then crushed into powder using a high-speed crusher to obtain a modified starch-based single-component intumescent flame retardant with itaconic acid as a bridge.

[0034] Wherein, the starch in step (1) is one or more of soluble starch and water-soluble starch.

[0035] The molar ratio of melamine to phosphoric acid used in step (3) is 1:(1-2).

[0036] The amount of DOPO-modified itaconic acid solution used in step (4) is calculated based on the molar ratio of DOPO to starch being 1:(1-2).

[0037] The amount of melamine phosphate solution used in step (5) is calculated based on the molar ratio of melamine to DOPO being 1:1.

[0038] The stirring speed in steps (1) to (5) is 200-500 rpm.

[0039] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0040] Example 1 Weigh 9 g (0.05 mol) of soluble starch in a beaker, add deionized water and stir at room temperature to prepare a starch suspension. Take another beaker, weigh 4.5 g (0.05 mol) of melamine in a beaker, add 80 mL of deionized water and stir at room temperature, take 5.8 mL of phosphoric acid (0.05 mol) in a measuring cylinder, slowly add it to the melamine solution, and stir it fully by magnetic stirring to obtain a melamine phosphate solution. Weigh 10.8 g (0.05 mol) of DOPO and 6.050 g (0.05 mol) of itaconic acid, pour them into a three-necked flask equipped with a magnetic stirrer, a reflux condenser, 80 mL of anhydrous ethanol and nitrogen, and raise the temperature to 90 ° C under stirring at 300 rpm. React for 2 h to obtain a DOPOIA solution. Slowly drop the prepared starch suspension into the DOPOIA solution, then raise the temperature to 120 ° C and react for 2 h. The temperature was lowered to 90°C under stirring at 500 rpm, and the prepared melamine phosphate was slowly added dropwise into the three-necked flask using a separatory funnel and reacted for 2 h. After the reaction, the product was allowed to settle for 24 h, then filtered and washed three times with anhydrous ethanol, dried at 80°C in a vacuum oven for 48 h, and then crushed into powder using a high-speed crusher to obtain the flame retardant DOPOIASST-1.

[0041] Example 2 Weigh 9 g (0.05 mol) of water-soluble starch in a beaker, add deionized water and stir at room temperature to prepare a starch suspension. Take another beaker, weigh 4.5 g (0.05 mol) of melamine in a beaker, add 80 mL of deionized water and stir at room temperature, take 11.6 mL of phosphoric acid (0.1 mol) in a measuring cylinder, slowly add it to the melamine solution, and stir it fully by magnetic stirring to obtain a melamine phosphate solution. Weigh 10.8 g (0.05 mol) of DOPO and 6.050 g (0.05 mol) of itaconic acid, pour them into a three-necked flask equipped with a magnetic stirrer, a reflux condenser, 80 mL of anhydrous ethanol and nitrogen, and raise the temperature to 90 ° C under stirring at 300 rpm. React for 2 hours to obtain a DOPOIA solution. Slowly drop the prepared starch suspension into the DOPOIA solution, then raise the temperature to 120 ° C and react for 2 hours. The temperature was lowered to 90°C under stirring at 500 rpm, and the prepared melamine phosphate was slowly added dropwise into the three-necked flask using a separatory funnel and reacted for 2 h. After the reaction, the product was allowed to settle for 24 h, then filtered and washed three times with anhydrous ethanol, dried at 80°C in a vacuum oven for 48 h, and then crushed into powder using a high-speed crusher to obtain the flame retardant DOPOIASST-2.

[0042] Comparative Example Take a beaker, weigh 4.5 g (0.05 mol) of melamine in the beaker, add 80 mL of deionized water and stir at room temperature, take 5.8 mL of phosphoric acid (0.05 mol) in a measuring cylinder, slowly add it to the melamine solution, and stir it fully by magnetic stirring to obtain a melamine phosphate solution. Weigh 10.8 g (0.05 mol) of DOPO and 6.050 g (0.05 mol) of itaconic acid, pour them into a three-necked flask equipped with a magnetic stirrer, a reflux condenser, 80 mL of anhydrous ethanol and nitrogen, and raise the oil bath temperature to 90°C under stirring at 300 rpm, react for 2 h, and obtain a DOPOIA solution. Under stirring at 500 rpm, the prepared melamine phosphate was slowly added dropwise into a three-necked flask using a separatory funnel and reacted for 2 h. After the reaction, the product was allowed to settle for 24 h, then filtered and washed three times, dried at 80 °C in a vacuum oven for 48 h, and then crushed into powder using a high-speed crusher to obtain the flame retardant DOPOIAMEL.

[0043] Application Examples 90 parts (mass fraction) of PLA were weighed and mixed with 10 parts (mass fraction) of flame retardant prepared in the example, 8 parts (mass fraction) of flame retardant prepared in the comparative example, 2 parts (mass fraction) of soluble starch and 10 parts (mass fraction) of single soluble starch respectively, and then extruded and granulated by a twin-screw extruder and injection molded to prepare standard vertical combustion (UL-94) (length × width × thickness = 130 mm × 10 mm × 3.2 mm), bar and dumbbell-shaped (length × width × thickness = 150 mm × 20 mm × 10 mm) mechanical properties standard test bar for testing. At the same time, pure PLA pellets were injection molded as a comparison.

[0044] The prepared vertical combustion specimens, limiting oxygen index specimens, standard compression specimens and composite materials were tested for combustion performance and mechanical properties. The test results are shown in Table 1.

[0045] Table 1 Flame retardant and mechanical properties test results

[0046] From the test results in Table 1, it can be seen that the vertical combustion test grade of pure PLA is NR, the LOI value is 19.8%, and the residual carbon rate is only 2.1%; the samples of the comparative flame retardant mixed with starch or using starch alone for flame retardancy have limited improvement in flame retardancy compared with pure PLA, and the serious condition of molten droplets has no significant improvement; while the samples using the flame retardant of the embodiment can reach V-0 level in the vertical combustion test, the LOI value is increased to more than 28.7%, and the residual carbon rate after full combustion is more than 8.2%. This proves that the flame retardant of the present invention has good compatibility when used in PLA, and the flame retardant effect of the burning strip is significantly improved.

[0047] At the same time, compared with pure PLA (tensile strength 58.2 MPa), the tensile strength of the samples in which the comparative flame retardant was mixed with starch or starch was used alone for flame retardancy decreased more (42.9 MPa and 40.3 MPa, respectively); while the samples using the flame retardant of the embodiment had a better flame retardant effect and a slight decrease in tensile strength (46.1 MPa and 47 MPa, respectively). It can be seen that the flame retardant prepared by the one-pot method of the present invention not only has a higher flame retardant efficiency, but also can better maintain the original mechanical properties of PLA.

[0048] Figure 1 The FT-IR images of the modified starch-based single-component intumescent flame retardant prepared in Examples 1 and 2, starch (SST), and melamine (MEL). From the spectra of DOPOIASST-1 and DOPOIASST-2, it can be seen that the FT-IR images at 1114.54 cm -1 、1175.01 cm -1The vibration absorption peak corresponding to POC (aromatic ring) indicates that DOPO was successfully modified onto itaconic acid; at 1658 cm -1 The characteristic peak of C=N appeared at the position of 1030 cm -1 The peak at 3600-3300 cm -1 There is a broad peak at , which may be the absorption peak of the hydroxyl group in starch. In summary, the infrared test confirmed the successful synthesis of the flame retardant.

[0049] Figure 2 , 3 The SEM images of the carbon layer after burning of the PLA specimens with modified starch-based flame retardants prepared by adding flame retardants of Example 1 and Example 2 are shown. It can be seen from the figure that the carbon layer is dense and compact without holes, which can effectively isolate heat transfer and has a good flame retardant effect.

[0050] Figure 4 The SEM image of the carbon layer of the combustion specimen prepared by adding the flame retardant obtained in the comparative example and the starch mixture after combustion. It can be seen from the figure that after full combustion, although the carbon layer is dense, some holes appear, which is not conducive to isolating heat and oxygen, and the flame retardant effect is not good.

[0051] Figure 5 This is a SEM image of the carbon layer of the combustion specimen prepared by adding only starch. It can be seen from the figure that it has large holes, cannot isolate heat transfer, and has almost no flame retardant effect.

[0052] Figure 6 This is a SEM image of the carbon layer of pure PLA specimens after combustion. It can be seen from the figure that the carbon layer of pure PLA after full combustion is fluffy and porous, which is not conducive to isolating heat and oxygen and has almost no flame retardant effect.

[0053] The weight of the degradation specimens prepared by adding the flame retardant obtained in Example 1, starch and pure PLA before and after degradation was recorded, and the weight change rate was calculated and plotted as follows: Figure 7 . From the results in the figure, it can be seen that the mass of different materials increases in the initial stage. It is speculated that this may be because the material absorbs water in the soil, resulting in an increase in mass. About 30 days after degradation, the degradation rates of the three began to diverge. Among them, the mass loss rate of the strips with the flame retardant added in Example 1 was the largest, followed by the strips with the addition of starch. The degradation rate of the pure PLA strips was much lower than the two. By 90 days, the pure PLA strips had only degraded by 0.002%, the strips with the addition of starch had degraded by 0.008%, and the strips with the addition of the flame retardant in Example 1 had degraded by 0.13%, and their degradation rates were greatly improved. In summary, it can be seen that the addition of the flame retardant of the present invention can accelerate the degradation rate of PLA.

[0054] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a modified starch-based single-component intumescent flame retardant using itaconic acid as a bridge, characterized in that: The following steps are involved: (1) Add starch to deionized water and stir magnetically at room temperature to obtain a starch suspension; (2) slowly adding itaconic acid and DOPO into anhydrous ethanol and stirring to react to obtain a DOPO-modified itaconic acid solution; (3) adding melamine to deionized water, stirring evenly to obtain a suspension, and then adding phosphoric acid to react to obtain a melamine phosphate solution; (4) adding the starch suspension obtained in step (1) dropwise into the DOPO-modified itaconic acid solution obtained in step (2), and obtaining a DOPO-modified starch suspension with itaconic acid as a bridge by stirring and reacting; (5) The melamine phosphate solution obtained in step (3) is added dropwise to the DOPO modified starch suspension obtained in step (4); after stirring for reaction and aging at room temperature, the mixture is vacuum filtered, washed, dried, and crushed to obtain a modified starch-based single-component intumescent flame retardant with itaconic acid as a bridge.

2. The preparation method according to claim 1, characterized in that: The starch in step (1) is one or more of soluble starch and water-soluble starch.

3. The preparation method according to claim 1, characterized in that: The molar ratio of itaconic acid to DOPO used in step (2) is 1:1; the temperature of the stirring reaction is 90° C. and the time is 2 h.

4. The preparation method according to claim 1, characterized in that: The molar ratio of melamine to phosphoric acid used in step (3) is 1:(1-2); the reaction temperature is 70-100°C and the reaction time is 2 h.

5. The preparation method according to claim 1, characterized in that: The amount of DOPO-modified itaconic acid solution used in step (4) is calculated based on the molar ratio of DOPO to starch being 1:(1-2); the stirring reaction is carried out at a temperature of 120° C. for a time of 1.0-2.0 h.

6. The preparation method according to claim 1, characterized in that: The amount of melamine phosphate solution used in step (5) is converted according to the molar ratio of melamine to DOPO of 1:1; the stirring reaction temperature is 70-100°C and the time is 2 h; the aging time is 12-24 h; the drying temperature is 70-100°C and the time is 12-24 h.

7. A modified starch-based single-component intumescent flame retardant using itaconic acid as a bridge, prepared by the method of any one of claims 1 to 6.

8. Use of the modified starch-based single-component intumescent flame retardant according to claim 7 in PLA, characterized in that: The modified starch-based single-component intumescent flame retardant is added to PLA in an amount of 5% to 15% of the mass of PLA.

Citation Information

Patent Citations

  • Phosphorus-containing flame retardant and preparation method thereof

    CN103772740A

  • Preparation method of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)-based halogen-free flame retardant polybutylece terephthalate (PBT) resin

    CN103881333A

  • Modified starch for preparing halogen-free flame-retardant TPV composite material and preparation thereof

    CN110964124A

  • Acidolysis-crosslinking-sulfonation composite modified starch slurry and preparation method thereof

    CN111234041A

  • Diesterified starch-based flame retardant and preparation method thereof, and starch-based flame-retardant finishing agent and preparation method and use

    GB2625848A